ROCKS MAGNETIC PROPERTIES AS CRITERIA OF THEIR ORE BEARING (ON THE BASE OF AZOV ORE DEPOSIT) - SUKHORADA, A.; POPOV, S.; STREKOZOV, S.; YUSHYN, O.; RESHETNIAK, M. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
Characters of Azov rare-metal deposits magnetic properties are described. Results of the study are evidences of considerable significance of magnetic researches for prediction of ore presence. It concerns mainly deposits connected with alkaline magmatism displaying of Priazovsky area.